Role of doxapram in reducing pulmonary complications after major surgery. Issue 6002 (17th January 1976) - Gawley, T H; Dundee, J W; Gupta, P K; Jones, C J
Abstract : In a double-blind study patients given a single dose of doxapram 1-5-2-0 mg/kg combined with morphine postoperatively had a significantly lower incidence of reflex postoperative cough and expectoration of purulent sputum than patients given morphine alone. They also had significantly higher arterial oxygen tensions five days postoperatively. Smaller differences were found with naloxone combined with morphine.